2018
DOI: 10.1089/ars.2017.7406
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Quinone Chelators: Properties, Mechanisms of Action, Cell Delivery, and Cell Toxicity

Abstract: To enhance their therapeutic effectiveness, and decrease cardiotoxicity and other side effects, we intend to conjugate the quinone chelators with monoclonal antibodies and peptide hormones that are specifically targeted to receptors on the cancer cell surface. Some such candidates have already been synthesized. An alternative approach for delivery of our compounds involves the use of specific peptide-based nanoparticles. In addition, our novel approach for treating malignancies is also suitable for photodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 55 publications
1
59
0
1
Order By: Relevance
“…The spectra were recorded by infusion into the ESI (Thermo-Fisher, San Josè, CA, USA) source dissolving the sample in MeOH. 1 Hz), 6.58 (1H, d, J = 8.9 Hz), 5.24 (1H, t), 5.10 (1H, t), 3.84 (6H, s), 3.80 (3H, s), 3.41 (2H, d, J = 6.9 Hz), 2.08 (2H, dd, J = 7.5, 6.9 Hz), 2.00 (2H, m), 1.81 (3H, s), 1.67 (3H, s), 1.60 (3H, s). 13 13 C and HRESIMS spectra are reported in Supporting Information (Figures S4-S6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra were recorded by infusion into the ESI (Thermo-Fisher, San Josè, CA, USA) source dissolving the sample in MeOH. 1 Hz), 6.58 (1H, d, J = 8.9 Hz), 5.24 (1H, t), 5.10 (1H, t), 3.84 (6H, s), 3.80 (3H, s), 3.41 (2H, d, J = 6.9 Hz), 2.08 (2H, dd, J = 7.5, 6.9 Hz), 2.00 (2H, m), 1.81 (3H, s), 1.67 (3H, s), 1.60 (3H, s). 13 13 C and HRESIMS spectra are reported in Supporting Information (Figures S4-S6).…”
Section: Methodsmentioning
confidence: 99%
“…Many classes of natural molecules have been conceived by nature to play specific roles in cell processes through selective interactions with key cellular targets. In this frame, quinones represent a clinically relevant class of chemotherapeutic agents with antitumor activity already described in several cell lines [1]. The most prominent chemical feature of these compounds, both natural and synthetic derivatives, is the ability to undergo redox cycling to generate reactive oxygen species (ROS), responsible for significant cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…While the exact mechanism of anthracycline‐induced cytotoxicity is still unknown, the production of highly reactive free radicals and reactive oxygen species (ROS) is a generally accepted mechanism. [ ][ ][ ] It arises from the presence of a quinone moiety that can be readily reduced by cellular reductants to yield a semiquinone radical . In aerobic conditions, semiquinones can reduce molecular oxygen resulting in the formation of ROS, which can initiate radical chain reactions leading to oxidative stress and ultimately cellular death .…”
Section: Introductionmentioning
confidence: 99%
“…[2][6] [21] It arises from the presence of a quinone moiety that can be readily reduced by cellular reductants to yield a semiquinone radical. [21] In aerobic conditions, semiquinones can reduce molecular oxygen resulting in the formation of ROS, which can initiate radical chain reactions leading to oxidative stress and ultimately cellular death. [6] Given the importance of redox-active metal ions in the mechanism of toxicity of anthracyclines, it has been suggested that metal-chelating quinone moieties could considerably increase the rate of ROS generation, thus leading to higher cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation